Kebijakan Pesantren Mu’adalah dan Implementasi Kurikulum di Madrasah Aliyah Salafiyah Pondok Tremas Pacitan - Ara Hidayat; Eko Wahib (Jurnal Pendidikan Islam, 2014)
This study is about the Mu’adalah Boarding School Policy and the Implementation of the curriculum at the Islamic Senior High School (Madrasah Aliyah) Salafi Tremas Pacitan. The educational institution of the Islamic boarding school is an inseparable part of the national educational system. This changes the mindset and point of view of the previous Islamic boarding school that was considered as a non-formal institution that did-not gets a good appreciation of its graduates. The research findings show that the mua’adah Islamic boarding school has been established as an institution that is equivalent to other formal educational institutions by the ministry of religion. The status of Salafiyah Islamicsenior high school is stronger. Furthermore, it must be improved directly its educational quality, teacher competences, and the curriculum implementation of the Islamic SeniorHigh School of Salafiyah Tremas Pacitan.